A five-phase 20-slot/18-pole PMSM for electric vehicles. Issue 2 (7th March 2016) - Sui, Yi; Zheng, Ping; Tang, Peilun; Wu, Fan; Wang, Pengfei
Abstract : Purpose: – The purpose of this paper is to investigate a five-phase permanent-magnet synchronous machine (PMSM) that features high-power density and high-fault-tolerant capability for electric vehicles (EVs). Design/methodology/approach: – The five-phase 20-slot/18-pole PMSM is designed by finite-element method. Two typical rotor structures which include Halbach array and rotor eccentricity are compared to achieve sinusoidal back electromotive force (EMF). The influence of slot dimensions on leakage inductance and short-circuit current is analyzed. The method to reduce eddy current loss of permanent magnets (PMs) is investigated. The machine performances under both healthy and fault conditions are evaluated. Finally, thermal behavior of the machine is studied by Ansys. Findings: – With both no-load and load performances considered, rotor eccentricity is proposed to reduce the harmonic contents of EMF. Increasing slot leakage inductance is an effective way to limit the short-circuit current. By segmenting PMs in circumferential direction, the PM eddy current loss is reduced and the machine efficiency is improved. With proper fault-tolerant control strategy, acceptable torque performance can be achieved under fault conditions. The proposed machine can safely operate under Class F insulation. Originality/value: – So far, many researches focus on multiphase PMSMs used in aviation fields, such as fuel pump and electric actuator. Differing from PMSMs used in aviation applications, machines for EVs require characteristics like wide speed ranges and variable operating conditions. Hence, this paper proposes a five-phase 20-slot/18-pole PMSM for EVs. The proposed design methodology is applicable to multiphase PMSMs with different slot/pole combinations.